2011
DOI: 10.1371/journal.pone.0025897
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cleft Lip on Adults' Responses to Faces: Cross-Species Findings

Abstract: Cleft lip and palate is the most common of the congenital conditions affecting the face and cranial bones and is associated with a raised risk of difficulties in infant-caregiver interaction; the reasons for such difficulties are not fully understood. Here, we report two experiments designed to explore how adults respond to infant faces with and without cleft lip, using behavioural measures of attractiveness appraisal (‘liking’) and willingness to work to view or remove the images (‘wanting’). We found that in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
53
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(60 citation statements)
references
References 25 publications
6
53
1
Order By: Relevance
“…The two studies looking at aesthetic and incentive salience of disfigured infant faces showed discrepant results. In one study [14], women gave higher ratings then men, but viewing time for faces with abnormalities did not differ between men and women. In the second study [13], men and women gave similar ratings for infant faces with abnormalities, but viewing time was longer for men than for women.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…The two studies looking at aesthetic and incentive salience of disfigured infant faces showed discrepant results. In one study [14], women gave higher ratings then men, but viewing time for faces with abnormalities did not differ between men and women. In the second study [13], men and women gave similar ratings for infant faces with abnormalities, but viewing time was longer for men than for women.…”
Section: Introductionmentioning
confidence: 90%
“…Two studies looked at the responses of men and women to infant faces with and without facial abnormalities [13], [14], one study looked at cute and less cute infant faces [15], and one study used computer-manipulated cute and less cute infant faces as well as attractive and less attractive adult faces [16]. In three of the four studies, women rated non-disfigured infant faces as more attractive than did men (‘liking’), but in a ‘pay per view’ task, both men and women showed the same effort to look at these faces (‘wanting’) [13], [14], [15]. In addition, cute infant faces were ‘liked’ and ‘wanted’ more by men and women than less cute infant faces [15].…”
Section: Introductionmentioning
confidence: 99%
“…These problems can at least partly be attributed to early disruptions in mother-child interactions—specifically a lack of all-important maternal responsiveness [83]. Non-parents report finding infants with cleft lip less “cute” than typical infants [84], and when viewing cleft-lip infant faces, early activity in the orbitofrontal cortex is significantly diminished compared to viewing typical infant faces [39, 84]. …”
Section: Difficulties In Prioritising Attentional Resporces To Cute Smentioning
confidence: 99%
“…A-D) Behavioural findings to images of human and animal with cleft lips show significantly stronger liking and wanting of non-cleft stimuli [84]. E) Neuroimaging findings of significantly diminished fast processing (<140ms) in OFC of cleft infant faces compared to cute infant faces in nonparents [39].…”
Section: Figurementioning
confidence: 99%
“…A plethora of recent studies have examined how adults respond to infant faces (Lobmaier, Bolte, Mast, & Dobel, 2010; Parsons, Young, Kumari, Stein, & Kringelbach, 2011; Parsons, Young, Parsons, et al, 2011; Sprengelmeyer et al, 2009). Adults have been shown to be remarkably attuned to infant facial configuration, and emerging evidence suggests that the specialized processing of infant faces may be supported by affective neural circuits (Kringelbach et al, 2008; Parsons, Young, Murray, Stein, & Kringelbach, 2010).…”
mentioning
confidence: 99%